2022
DOI: 10.1038/s41598-022-20286-5
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of micro-pores in Ni–Cr alloys via molten salt dealloying

Abstract: Porous materials with high specific surface area, high porosity, and high electrical conductivity are promising materials for functional applications, including catalysis, sensing, and energy storage. Molten salt dealloying was recently demonstrated in microwires as an alternative method to fabricate porous structures. The method takes advantage of the selective dissolution process introduced by impurities often observed in molten salt corrosion. This work further investigates molten salt dealloying in bulk Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Although not well studied so far, this family of molten salts offers interesting characteristics compared to molten carbonates, such as their lower melting temperature implying a lower energy cost, their high solubility of gases such as halogens 3 and CO 2 (which limits toxic emissions), and their high solubility of oxides, glasses and plastics. [13][14][15] In his study, Flandinet et al demonstrated the benets of molten hydroxides for the recovery of metals from WEEE also leading to production of H 2 , which can potentially be recovered.…”
Section: Introductionmentioning
confidence: 99%
“…Although not well studied so far, this family of molten salts offers interesting characteristics compared to molten carbonates, such as their lower melting temperature implying a lower energy cost, their high solubility of gases such as halogens 3 and CO 2 (which limits toxic emissions), and their high solubility of oxides, glasses and plastics. [13][14][15] In his study, Flandinet et al demonstrated the benets of molten hydroxides for the recovery of metals from WEEE also leading to production of H 2 , which can potentially be recovered.…”
Section: Introductionmentioning
confidence: 99%
“…formation of a micron-scale bicontinuous porous structure. [15][16][17][18][19][20][21] The phenomenon of dealloying corrosion is of particular concern as the dealloyed layer can become vulnerable to stress corrosion cracking 22 and/or hot spot formation [13] during heat transfer that endangers the Gen-IV reactor application. The phenomenon of dealloying corrosion has garnered considerable interest, particularly due to its prevalence at high homologous temperatures.…”
mentioning
confidence: 99%
“…In a collection of investigations led by Chen-Wiegart et al, [16][17][18]32,33 using in-situ synchrotron X-ray nano-tomography, the authors observed the formation of bicontinuous porous structure on Ni20Cr (wt%) microwires and thin foils at both nano and micron scale when statically exposed to molten chlorides (e.g. KCl-MgCl 2 ) between 500 °C and 800 °C.…”
mentioning
confidence: 99%
See 2 more Smart Citations